Snow modeling to predict surface contamination of cars - Bangalore Narahari, Tejas Sharma; Bharadhwaj, Yashas (My University, 2021)
Passenger safety and autonomous transportation have been few of the important innovations in the development of modern-day cars amongst the top-tier automobile manufacturers. Correspondingly, innovation in the level of passenger safety has evolved from just passive safety systems towards enhanced active safety systems such as Advanced Driver Safety System (ADAS), in recent times. Such systems are generally comprised of various sub-systems including radar sensors, cameras, etc. Contamination or exterior soiling on these is one of the major issues at hand that are hindering their functionalities. Contamination due to snow being one of the bigger issues under winter condi tions poses a significant challenge towards its functionalities which needs to be addressed. Field testing and wind tunnel experiments are being used traditionally at Volvo Cars to address the above issue. As a scope of this project, the challenge is to develop a model which predicts the snow contamination on automotive cars or bluff bodies using a Multi-phase CFD simulation approach. An aerodynamic analysis is initially performed to understand the flow features around the subject of interest. Later, particle simulation using the Lagrangian Particle Tracking method to study snow deposition is performed. To contrast with the results from simulation, wind tunnel experiments with similar test conditions are conducted over two bluff bodies, a Wedge section and an Ahmed body subjected to snow. The simulation results and experimental results are then compared with each other to analyse the deposition pattern in both real-world conditions and simulations.
Keywords: Multi-phase Modeling, Lagrangian Particle Tracking, Snow, Wind Tunnel Testing, Wedge, Ahmed Body